Characteristics of PMSE associated with the geomagnetic disturbance driven by corotating interaction region and high‐speed solar wind streams in the declining solar cycle 23. Issue 4 (22nd April 2015) - Lee, Young‐Sook; Kirkwood, Sheila; Kwak, Young‐Sil; Shepherd, Gordon G.; Kim, Kyung‐Chan; Yang, Tae‐Yong; Kero, Antti
Abstract We report interannual variations of the correlation between the reflectivity of polar mesospheric summer echoes (PMSEs) and solar wind parameters (speed and dynamic pressure), and AE index as a proxy of geomagnetic disturbances, and cosmic noise absorption (CNA) in the declining phase (2001–2008) of solar cycle 23. PMSEs are observed by 52 MHz VHF radar measurements at Esrange (67.8°N, 20.4°E), Sweden. In approaching the solar minimum years, high‐speed solar wind streams emanate from frequently emerging coronal holes, leading to 7, 9, and 13.5 day periodicities in their arrival at Earth. Periodicities of 7 and/or 9 days are found in PMSE reflectivity in 2005–2006 and 2008. Periodicity‐resolved correlations at 7 and 9 days of both D region ionization observed by cosmic noise absorption (CNA) and PMSE with solar wind speed and AE index vary from year to year but generally increase as solar minimum is approached. PMSEs have a higher periodicity‐resolved correlation with AE index than the solar wind speed. In addition, cross correlation of PMSE reflectivity with AE index is mostly higher than with CNA in solar minimum years (2005–2008). This can signify that high‐speed solar wind stream‐induced high‐energy particles possibly have strong influence on CNA, but not as much as on PMSE, especially for the years of significant periodicities occurring.